Correlation between epicardial adipose tissue and myocardial injury in patients with COVID-19 - Su, Tianhong; Zhong, Bincheng; Tang, Chao; Qiao, Shunsong; Feng, Yu; Peng, Hao; Gu, Xiaosong (Frontiers in Physiology, 2024)
Background: Many people infected with COVID-19 develop myocardial injury. Epicardial adipose tissue (EAT) is among the various risk factors contributing to coronary artery disease. However, its correlation with myocardial injury in patients diagnosed with COVID-19 remains uncertain. Methods: We examined myocardial biomarkers in population affected by COVID-19 during the period from December 2022 to January 2023. The patients without myocardial injury were referred to as group A (n = 152) and those with myocardial injury were referred to as group B (n = 212). Results: (1). The A group and the B group exhibitedstatistically significant differences in terms of age，TC, CRP, Cr, BUN, LDL-C, IL-6, BNP, LVEF and EAT (P＜0.05). (2). EAT volumehad a close relationship with IL-6，LDL-C, cTnI, and CRP (P< 0.05); the corresponding correlation coefficient values were 0.24, 0.21, 0.24, and 0.16. In contrast to those with lower EAT volume, more subjects with a higher volume of EAT had myocardial injury(P＜0.05). Regression analysis showed that EAT, LDL-C, Age and Cr were established as independent risk variables for myocardial injury in subjects affected by COVID-19. (3). In COVID-19 patients, the likelihood of myocardial injury rised notably as EAT levels increase. (p<0.001). Addition of EAT to the basic risk model for myocardial injury resulted in improved reclassification. (Net reclassification index: 58.17%, 95% CI: 38.35%, 77.99%, p < 0.001). Conclusion: Patients suffering from COVID-19 with higher volume EAT was prone to follow myocardial injury and EAT was an independent predictor of heart damage in these individuals.